Genetic Structure and Conservation Management of Endemic Salix kusanoi in Fragmented Habitats of Taiwan - Piumi Chathurika Palangasinghe; Ya-Zhu Ko; Tsai-Wen Hsu; Manupa Pabasara Wickramasinghe; Huei-Chuan Shih; Meng-Shin Shiao; Yu-Chung Chiang (Plants)
Salix kusanoi is an endangered riparian tree species endemic to Taiwan. This study aimed to evaluate the genetic diversity and population structure across eight fragmented populations employing 33 microsatellite loci. The findings revealed moderate genetic diversity (mean AE = 3.85, HO = 0.22) and significant deviations from the Hardy–Weinberg equilibrium. This indicated an evolutionary pressure, such as genetic drift and inbreeding. The Analysis of Molecular Variance (AMOVA) demonstrated evident genetic differentiation among populations (FST = 0.30). Principal Coordinates Analysis (PCoA) and Bayesian clustering (STRUCTURE) described distinct regional genetic patterns, with K = 5 providing a robust context for understanding localized genetic variation. Conservation interventions, including targeted in situ conservation for genetically unique populations (SBF) and genetic rescue strategies for genetically underprivileged populations (NW and NT), are proposed to safeguard the genetic integrity and adaptive potential of S. kusanoi.